From Sakinah to Cyber-Conflict: Paul Ricoeur’s Hermeneutics and the Surplus Meaning of BP4 Texts in the Digital Era - Elismayanti Rambe; Siti Rahma Harahap; Nurliana; Nanang Arianto; L.L.M Nur Syakirah Binto Mohd Adnan (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2025)
This study examines the construction of meaning in the official text of the Marriage Advisory, Development, and Preservation Agency (BP4), which has rarely been analyzed through a hermeneutic lens. Previous research has focused primarily on BP4’s institutional performance, leaving a gap in understanding how its textual discourse shapes the concept of a harmonious family and how these meanings shift in the digital era. The purpose of this study is to analyze the symbolic structure of the BP4 text, interpret its key concepts, and explore how its meanings are recontextualized within contemporary digital family dynamics. This research employed Paul Ricoeur’s hermeneutic framework, combining structural analysis, symbolic interpretation, and appropriation. Primary data are drawn from the BP4 book Foundations of a Sakinah Family, particularly chapters on sakinah family ideals, family communication, and conflict management. Data were analyzed through textual coding, thema¬tic mapping, and interpretive triangulation. The findings show that the BP4 text constructs a harmonious family as a dynamic ethical process grounded in sakinah, mawaddah, and rahmah. The text frames commu¬nication through the principle of qaulan as a moral discipline that regulates emotional expression and relational balance. The study also identifies a transformation of meaning when the text interacts with digital realities, including the reinterpretation of sakinah and islah in relation to cyber infidelity, platform-based communication aggression, and digital psychological stress. These findings highlight the need to update BP4 materials to address digital-era challenges. The study concludes that Ricoeur’s hermeneutics provides a productive framework for renewing state religious literature and strengthening its relevance for contemporary Muslim families.